DAMPAK ALFAMART TERHADAP PENDAPATAN USAHA MIKRO DI KELURAHAN PAAL MERAH KOTA JAMBI - Putri Hadjrahtul Aswad Lubis; Novi Mubyarto; Ahmad Syahrizal (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2023)
This research was conducted to oblain information about the impact of Alfamart on the income of micro businesses in Paal Merah Village, Jambi City. This research was conducted directly in the field using qualitative research, namely with interviews conducted in a relaxed manner, not complicating traders, and the questions asked were not interrogative but only to obtain the data needed to complete and complete the writing in this study. The results showed that before there was Alfamart the income of traders was around Rp. 1.000.000 – Rp. 6.000.000, but after the presence of Alfamart their income decreased to only Rp. 600.000 – Rp. 3.000.000 while the other 2 stores earn a steady income. One of the factors that decrease Alfamart’s income is the distance between small traders and Alfamart which is too close and the good and comfortable service provided by Alfamart. Thus, the role of strategy is very important for small traders in general, by arranging a good and comfortable store, increasing trading hours, and adding complete types of goods needed by the surrounding community, as well as good service to comsumers.